Anthropometric parameters for the female handball talents gaining from "Ormani Arenado Llonch" Initial Sport School of 15-18 years senior category - Luis Alberto Hernández-Pérez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2014)
This work approaches an important and present time problem for the staff that is working directly with handball sport training, because it treats aspects that are kept in the talents selection having as general objective to propose anthropometric parameters to attract female handball talentns from "Ormani Arenado Llonch" Initial Sport School of 15-18 years senior category. It was carried out a wide and detailed bibliographical revision about the topic, as well as interviews addressed to specialists that are part of the team management system with the objective of proposing anthropometric parameters for the gainig, allowing to determine the current necessities of this pedagogic process, as well as to establish these parameters to facilitate this process and making it more effective.